Iminenţa noii paradigme a bunăstării umane - un consum decent pentru toţi oamenii - Stanciu, Mariana (Calitatea Vieții, 2008)
The high concern for continuous increasing of the rich and powerful’s welfare is responsible for the worldwide environmental destruction – directly, through their control of the resources distribution, and indirectly, through influencing the adoption of consumerist practices by the other social classes. Starting from 1980, humans have consumed resources regularily much faster than the Earth could regenerate them. In nature, such peaks are followed by species collapse. This phenomenon is known, but considering the powerfuls’ actions, it seems that, at least for now, things are going quite according to their interests. The poor are caught in a vicious cycle in which environmental and social crises feed on each other. They are the first to be robbed of food sources, driven out by drought or flood. All these are not supposed to go further in this way. Mankind has to search and find a new paradigm of welbeing, by meeting general needs, practicing an ecological and moral economy.